Students’ Perception of Using Podcasts in EFL Listening Classes - Elawati, Teti; Rahmah, Mida Maulida; Mawaddah, Muna; Tarihoran , Naf’an (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2026)
This study aims to investigate students’ perceptions, benefits, and challenges in using podcasts for learning English listening in EFL contexts. This research employed a quantitative method using a questionnaire distributed to 102 students. The findings reveal that students generally have positive perceptions of podcasts, as they consider them interesting and enjoyable learning media. In terms of benefits, podcasts help improve students’ listening comprehension, pronunciation, vocabulary, motivation, and understanding of different English accents. However, several challenges were also identified, including unfamiliar vocabulary, fast speech rate, difficulty in maintaining focus, and challenges in understanding certain topics. These challenges are categorized as moderate. Overall, the study concludes that podcasts are an effective and engaging tool for improving students’ listening skills, although appropriate guidance is needed to maximize their effectiveness.